The factors that influence transfer of training among employees at Malaysian Palm Oil Board (MPOB), Bangi / Hadibah Nurfatin Hanuar - Hanuar, Hadibah Nurfatin (Faculty of Business and Management, 2010)
Training is a part of organization activities to help and improve employee’s performance. If employees can improve their performance, company can increase their productivity and so, will increase the company sales. This research was conducted to determine the factors that influence transfer of training among employees at Malaysian Palm Oil Board (MPOB), Bangi. The main objective is to examine the factors that lead to transfer of training at Malaysian Palm Oil Board (MPOB), Bangi. The relationship between the factors (motivation, training design, and work environment) with transfer of training was investigated in a sample of 50 employees by using questionnaires. Result showed that the most influential factor is work environment. Recommendation for future research also has been discussed.